SISTEM DIGITAL PENGAJUAN PINJAMAN DI KOPERASI AL HIKMAH SEMESTA CABANG PEGANDON - Edy Siswanto; Munifah Munifah; Ahmad Syauqi (Jurnal Riset Teknik Komputer, 2024)
Al Hikmah Semesta Cooperative, Pegandon Branch, is a savings and loans office that helps the community in terms of business financing, agricultural capital, savings in the form of deposits, a cooperative structure that provides loans to customers, interest rates on various credits, etc. Problems with the Al Hikmah Semesta Cooperative loan application system, Pegandon Branch. This system still uses a manual system where data is collected via the Excel application, which is of course vulnerable to data loss and damage. The information system of the Al Hikmah Semestah Community Cooperative Pegundon Branch will make the provision of financial information to users of financial reports more effective and precise. The success of the role of the information system can be measured from the effectiveness of presenting borrower data reports. If the loan application information system plays a good role in its implementation, this system can produce effective and high-quality borrower data reports that become the basis for decision making.